Orbital cycle records in shallow unconsolidated sediments: implications for global carbon cycle and hydrate system evolution in deep-sea area sediments of the Qiongdongnan Basin - Yang Dong; Yang Dong; Ren Wang; Ren Wang; Jinqiang Liang; Yulin He; Jinfeng Ren; Wanzhong Shi; Wanzhong Shi; Xiaosong Wei; Xiaosong Wei; Hao Du; et al. (Frontiers in Marine Science)
IntroductionMilankovitch theory has extensive application in sequence stratigraphy and the establishment of time scales. However, it is rarely applied to shallow strata rich in hydrates. Cyclostratigraphic analysis of the Quaternary unconsolidated sediments can help identify climate and sea level changes that correspond to orbital cycles and improve our understanding of the dynamic evolution of hydrates.MethodsUsing the natural gamma-ray log data from the deepwater area well W01 in the Qiongdongnan Basin, Milankovitch cycle analysis was conducted to identify the primary astronomical period in W01. Anchored to existing AMS-14 C age from bivalve shell as reference point, an astronomical age scale of W01 was established. Simultaneously, through the analyses of major trace elements and total organic carbon content (TOC) in sediment samples, how astronomical orbital cycles influenced past environmental conditions. Furthermore, employing sedimentary noise models, the relative sea level change of well W01 was reconstructed.ResultsSedimentary cycles of 27.34 m and 6.73 m were identified in the GR data from well W01, corresponding to orbital periods of 405 kyr and 100 kyr eccentricity, with a duration of approximately 2.5 Myr. The spectral analysis of paleoenvironmental proxies reveals a sedimentary cycle of approximately 27 m, while the sedimentary noise model reconstructs the fluctuating rise in sea level change. An obliquity modulation period of approximately 170 kyr was identified in the TOC data, which may reflect the combined effects of obliquity and other orbital parameters.DiscussionSpectral analysis of paleoenvironmental indicators showed that long eccentricity cycle had varying degrees of influence on changes in paleoclimate, paleosalinity, and paleoredox conditions. Additionally, a 1.2 Myr cycle was identified as a significant factor influencing sea level changes during the early Pleistocene in the South China Sea (SCS). In addition, it is confirmed that the dominant period of the glacial-interglacial cycle in the SCS from 0.6 Ma to the present is 100 kyr period. Synthesize the above analysis, during phases of low amplitude in the 405 kyr cycle or minimum value of the 100 kyr cycle, which are associated with lower temperature, conditions become more conducive to hydrate accumulation.